A method for preparing high-density quartz sand
By mixing white carbon black with organic silane to generate high-density quartz sand, the problem of insufficient density in quartz crucibles is solved, the density and production efficiency of quartz sand are improved, the cost is reduced, and the product yield is achieved.
Patent Information
- Application Number
- CN202310406173.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-04-17
AI Technical Summary
The density level of existing high-purity quartz sand is insufficient, resulting in the inability to form uniformly during the preparation of quartz crucibles, affecting the crystal growth quality and high production costs.
The industrial gas-phase white carbon black is used as the precursor seed crystal and organic silane to form high-density quartz sand through hydrolysis reaction, and a gel network is formed by constant pressure dropping equipment and mechanical stirring. Then it is dried in a vacuum environment and roasted at high temperature. Made high-density quartz sand.
The tap density of quartz sand is improved, the problem of insufficient density is solved, the amount of organosilane is reduced, the production cost is reduced, and the product yield is improved.
Smart Images

Figure CN116462201B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-purity quartz sand preparation, in particular to a method for preparing high-density quartz sand. Background Art
[0002] Due to its good high temperature resistance and thermal stability, high-purity quartz sand is mainly used to manufacture quartz crucibles for pulling single crystal silicon. Quartz crucibles are essential consumables for pulling single crystal silicon rods. Their production is quite cumbersome and requires a multi-layer design. The outer layer of the crucible usually requires a lower density to make the crucible a good insulator, while the inner layer must be prepared into a bubble-free layer with high density and high strength to avoid the slight disturbance of bubbles to the melt or the small amount of impurities released by the bubble openings that affect the growth of the crystal. High-purity quartz sand prepared by chemical synthesis is mainly used to prepare the inner layer of sand for quartz crucibles. If the density grade of the quartz sand used is not enough, during the preparation of the quartz crucible, the quartz sand will not be able to be evenly spread in the mold by centrifugal force. Therefore, exploring the influence of bubbles and impurities in the inner layer of the crucible on crystal growth plays an important role in improving the efficiency of the photovoltaic power generation industry.
[0003] At present, most of the research on quartz crucibles focuses on its structure or the migration of crucible impurities, bubble evolution, cristobalite formation and crucible coating during a single crystal pulling process. However, for the raw material of high-purity quartz sand for preparing crucibles, people pay more attention to the purity grade, impurity element content and hydroxyl content of quartz sand, and rarely study its density. Summary of the invention
[0004] In view of the above-mentioned technical deficiencies, the purpose of the present invention is to provide a method for preparing high-density quartz sand, using industrial fumed silica as a precursor seed silicon source and mixing it with organic silane to obtain a high-density, cost-controlled high-purity quartz sand sample.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A method for preparing high-density quartz sand comprises the following steps:
[0007] S1. Add ultrapure water with a resistivity of >18MΩ·cm into a beaker, and then add acid solution to make the aqueous solution present an acidic environment to obtain an acidic solution;
[0008] S2, uniformly dispersing the organosilane in the alcohol solution to obtain a mixed solution, and adding the mixed solution to a constant pressure dripping device;
[0009] S3, adding the mixed solution in step S2 to the acidic solution prepared in step S1 by a constant pressure dripping device, heating after the dripping is completed, aging and alcohol removal are performed during the constant temperature process, and ultrapure aqueous solution is continuously added during the alcohol removal process to keep the quality of the solution the same as before the heating, control the pH of the solution, and obtain silica sol through a hydrolysis reaction;
[0010] S4. Add ultrapure water with a resistivity of more than 18 MΩ·cm into a beaker, then add white carbon black, and stir continuously to make the white carbon black evenly dispersed in the aqueous solution to obtain a precursor silicon source seed crystal;
[0011] S5, adding the precursor silicon source seed crystal prepared in step S4 to the silica sol prepared in step S3, stirring continuously, adjusting the pH value of the solution with ammonia water, and stirring mechanically for 0.5-4h;
[0012] S6. Stop stirring after the gelation reaction occurs, and place at 30°C under normal pressure for 1-10 days until the gel network hardens;
[0013] S7, spreading the aged gel in step S6 on a watch glass, drying it in a vacuum environment, and sieving and grading it after natural cooling;
[0014] S8. Place the sample classified in step S7 in a quartz boat and calcine it at high temperature for 3-6 hours in an air atmosphere to obtain high-density quartz sand.
[0015] Preferably, in step S1, the acid solution is any one of hydrochloric acid, sulfuric acid and nitric acid; the pH of the prepared acidic solution is 1-2; and the molar ratio of the acid solution to ultrapure water is 0.0012-0.0045:6.
[0016] Preferably, in step S2, the organosilane is any one of tetramethoxysilane or tetraethoxysilane; the alcohol solution is any one of methanol, ethanol and isopropanol; and the molar ratio of the organosilane to the alcohol solution is 1:0-6.
[0017] Preferably, in step S3, the dropping speed is controlled at 0.5-8 ml / min; the constant temperature aging and alcohol removal temperature is controlled at 55° C.-75° C., the time is controlled at 1-6 h, and the pH is 1-2.
[0018] Preferably, in step S4, the specific gravity of the white carbon black is 80-200 g / cm 3 .
[0019] Preferably, in step S5, the concentration of the aqueous ammonia is 1%-27%; and the speed of the mechanical stirring is 100-1600 r / min.
[0020] Preferably, in step S7, the drying temperature is 100°C-250°C; and the mesh number of the sieve used for sieving and grading is 50-200.
[0021] Preferably, in step S8, the calcination temperature is 800°C-1400°C.
[0022] Preferably,
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention uses white carbon black and organic silane as silicon sources to prepare a quartz sand product. Compared with the quartz sand product prepared by using only organic silane, the tap density of the sample is greatly improved, which solves the problem that the quartz sand cannot be evenly spread under the action of centrifugal force due to insufficient density grade in the subsequent application process; white carbon black is used to replace part of the organic silane, which reduces the amount of the organic silicon source and saves production costs; white carbon black is used as a precursor seed crystal, which accelerates the rapid hydrolysis and condensation of the organic silane, avoids the waste of the organic silicon source, and thus improves the product yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of quartz sand samples prepared for BTH-TEOS and TEOS-TEOS;
[0026] Figure 2 FT-IR patterns of quartz sand samples prepared for BTH-TEOS and TEOS-TEOS. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0028] Example 1
[0029] A method for preparing high-density quartz sand comprises the following steps:
[0030] S1. At room temperature and pressure, add 25 g of ultrapure water into a beaker, adjust the pH of the solution to 1.5 with aqueous hydrochloric acid, stir at a speed of 1200 r / min, and stir for 10 min;
[0031] S2. At room temperature and pressure, add 48 g of tetraethoxysilane (TEOS) to 42 g of anhydrous ethanol, stir evenly with a glass rod, and then add the mixture to a constant pressure dripping device;
[0032] S3, under normal temperature and pressure, the mixed solution in step S2 is added dropwise to the acidic solution in step S1 at a rate of 4 ml / min, and heating is turned on after the addition is completed. When the temperature is raised to 71°C, constant temperature aging is performed to remove alcohol. The aging time is 2.5 h. Ultrapure water is continuously added during the alcohol removal process to keep the solution quality the same as before heating. The pH is controlled at 1-2 and the stirring speed is 1200 r / min. After the aging is completed, the heating is turned off and the solution is allowed to cool naturally;
[0033] S4. At room temperature and pressure, add 90 g of ultrapure water and 16 g of white carbon black (BTH) into a beaker, stir with a magnetic stirrer or a glass rod to evenly mix the white carbon black in the ultrapure water without small spherical particles, and stir for 30 min.
[0034] S5, slowly adding the white carbon black precursor seed crystals obtained in step S4 to the silica sol obtained in step S3, stirring evenly, adjusting the solution pH to 4 with ammonia water, stirring continuously for 2.5 hours, and stopping stirring immediately when a gelation reaction occurs;
[0035] S6, aging the gel prepared in step S5 at 30° C. for 72 h under normal pressure to harden the gel network;
[0036] S7, spreading the aged gel in step S6 on a watch glass, drying it in a vacuum environment with a vacuum degree of -0.1 MPa, drying it at 105°C for 5 hours, and then grinding, screening and grading it after natural cooling;
[0037] S8. Place the 50-200 mesh sample sieved and graded in step S7 in a quartz boat, and calcine it at 1400° C. for 3 hours in an air atmosphere to obtain a quartz sand sample.
[0038] Example 2
[0039] A method for preparing high-density quartz sand comprises the following steps:
[0040] S1. At room temperature and pressure, add 25 g of ultrapure water into a beaker, adjust the pH of the solution to 1.5 with hydrochloric acid aqueous solution, stir at a speed of 600 r / min, and stir for 10 min;
[0041] S2. At room temperature and pressure, add 48 g of tetraethoxysilane (TEOS) to 42 g of anhydrous ethanol, stir evenly with a glass rod, and then add the mixture to a constant pressure dripping device;
[0042] S3, under normal temperature and pressure, the mixed solution in step S2 is added dropwise to the acidic solution in step S1 at a rate of 4 ml / min, and heating is turned on after the addition is completed. When the temperature is raised to 71°C, constant temperature aging is performed to remove alcohol. The aging time is 2.5 h. Ultrapure water is continuously added during the alcohol removal process to keep the solution quality the same as before heating. The pH is controlled at 1-2 and the stirring speed is 1200 r / min. After the aging is completed, the heating is turned off and the solution is allowed to cool naturally;
[0043] S4. At room temperature and pressure, add 90 g of ultrapure water and 16 g of white carbon black into a beaker, stir with a magnetic stirrer or a glass rod to evenly mix the white carbon black in the ultrapure water without small spherical particles, and stir for 30 min.
[0044] S5, slowly adding the white carbon black precursor seed crystals obtained in step S4 to the silica sol obtained in step S3, stirring evenly, adjusting the solution pH to 4 with ammonia water, stirring continuously for 2.5 hours, and stopping stirring immediately when a gelation reaction occurs;
[0045] S6, aging the gel prepared in step S5 at 30° C. for 72 h under normal pressure to harden the gel network;
[0046] S7, spreading the aged gel in step S6 on a watch glass, drying it in a vacuum environment with a vacuum degree of -0.1 MPa, drying it at 105°C for 5 hours, and then grinding, screening and grading it after natural cooling;
[0047] S8. Place the 50-200 mesh sample sieved and graded in step S7 in a quartz boat, and calcine it at 1400° C. for 3 hours in an air atmosphere to obtain a quartz sand sample.
[0048] Example 3
[0049] A method for preparing high-density quartz sand comprises the following steps:
[0050] S1. At room temperature and pressure, add 25 g of ultrapure water into a beaker, adjust the pH of the solution to 1.5 with hydrochloric acid aqueous solution, stir at a speed of 1200 r / min, and stir for 10 min;
[0051] S2. At room temperature and pressure, add 48 g of tetraethoxysilane (TEOS) to 42 g of anhydrous ethanol, stir evenly with a glass rod, and then add the mixture to a constant pressure dripping device;
[0052] S3, under normal temperature and pressure, the mixed solution in step S2 is added dropwise to the acidic solution in step S1 at a rate of 8 ml / min, and heating is turned on after the addition is completed. When the temperature is raised to 71°C, constant temperature aging is performed to remove alcohol. The aging time is 2.5 h. Ultrapure water is continuously added during the alcohol removal process to keep the solution quality the same as before heating. The pH is controlled at 1-2 and the stirring speed is 1200 r / min. After the aging is completed, the heating is turned off and the solution is allowed to cool naturally;
[0053] S4. At room temperature and pressure, add 90 g of ultrapure water and 16 g of white carbon black into a beaker, stir with a magnetic stirrer or a glass rod to evenly mix the white carbon black in the ultrapure water without small spherical particles, and stir for 30 min.
[0054] S5, slowly adding the white carbon black precursor seed crystals obtained in step S4 to the silica sol obtained in step S3, stirring evenly, adjusting the solution pH to 4 with ammonia water, stirring continuously for 2.5 hours, and stopping stirring immediately when a gelation reaction occurs;
[0055] S6, aging the gel prepared in step S5 at 30° C. for 72 h under normal pressure to harden the gel network;
[0056] S7, spreading the aged gel in step S6 on a watch glass, drying it in a vacuum environment with a vacuum degree of -0.1 MPa, drying it at 105°C for 5 hours, and then grinding, screening and grading it after natural cooling;
[0057] S8. Place the 50-200 mesh sample sieved and graded in step S7 in a quartz boat, and calcine it at 1400° C. for 3 hours in an air atmosphere to obtain a quartz sand sample.
[0058] Comparative Example 1
[0059] A method for preparing high-density quartz sand comprises the following steps:
[0060] S1. At room temperature and pressure, add 25 g of ultrapure water into a beaker, adjust the pH of the solution to 1.5 with aqueous hydrochloric acid, stir at a speed of 1200 r / min, and stir for 10 min;
[0061] S2. At room temperature and pressure, add 48 g of tetraethoxysilane (TEOS) to 42 g of anhydrous ethanol, stir evenly with a glass rod, and then add the mixture to a constant pressure dripping device;
[0062] S3, under normal temperature and pressure, the mixed solution in step S2 was added dropwise to the acidic solution in step S1 at a rate of 4 ml / min, and heating was turned on after the addition was completed. When the temperature was raised to 55°C, constant temperature aging was performed for 3.5 hours, the pH was controlled at 1-2, the stirring speed was 1200 r / min, and the heating was turned off after the aging was completed, and the solution was allowed to cool naturally;
[0063] S4. At room temperature and pressure, add 25 g of ultrapure water and 16 g of anhydrous ethanol into a beaker, adjust the pH of the solution to 9-10 with ammonia water, stir at a speed of 1200 r / min, and stir for 10 min;
[0064] S5. At room temperature and pressure, add 32 g of tetraethoxysilane (TEOS) to 17 g of anhydrous ethanol, stir evenly with a glass rod, and then add the mixture to a constant pressure dripping device;
[0065] S6, under normal temperature and pressure, the mixed solution in step S5 is added dropwise to the alkaline solution in step S4 at a rate of 4 ml / min, and heating is turned on after the addition is completed. When the temperature is raised to 71°C, constant temperature aging is performed to remove alcohol. The aging time is 2.5 h. Ultrapure water is continuously added during the alcohol removal process to keep the solution quality the same as before heating. The pH is controlled at 9.0 and the stirring speed is 1200 r / min. After the aging is completed, the heating is turned off and the solution is allowed to cool naturally;
[0066] S7, slowly adding the alkaline silica gel prepared in step S6 to the silica sol prepared in step S3, stirring evenly, adjusting the pH value of the solution to 4 with ammonia water, stirring continuously for 3.5 hours, and stopping stirring immediately when a gelation reaction occurs;
[0067] S8, aging the gel obtained in step S7 at 30° C. for 72 hours under normal pressure to harden the gel network;
[0068] S9, spreading the aged gel in step S8 on a watch glass, drying it in a vacuum environment with a vacuum degree of -0.1 MPa, drying it at 105°C for 5 hours, and then grinding, screening and grading it after natural cooling;
[0069] S10, placing the 50-200 mesh sample sieved and graded in step S9 in a quartz boat, and calcining it at 1400° C. for 3 hours in an air atmosphere to obtain a quartz sand sample.
[0070] According to density test, the tap density of quartz sand in Examples 1, 2, and 3 is 1400 g / dm 3 , 1066g / dm 3 , 1193g / dm 3 The tap density of the quartz sand in Comparative Example 1 is 795 g / dm 3 ;
[0071] According to the yield test, the final yield of the quartz sand in Example 1 is 45%, while the final yield of the quartz sand in the comparative example is only 21%.
[0072] It can be concluded that the tap density of the quartz sand prepared under different experimental conditions is different, and the quartz sand prepared by the preparation method in Example 1 can obtain a better tap density. Compared with the quartz sand prepared by using tetraethoxysilane (TEOS) as the silicon source, the quartz sand sample prepared by adding part of white carbon black can obtain a higher sample yield.
[0073] Taking tetraethoxysilane (TEOS) as the organosilane, the hydrolysis process is as follows:
[0074] (1) Hydrolysis reaction
[0075] (2) Condensation reaction
[0076]
[0077] (3) Polymerization reaction
[0078]
Claims
1. A method for preparing high-density quartz sand, characterized in that: The following steps are involved: S1. Add ultrapure water with a resistivity of >18MΩ·cm into a beaker, and then add acid solution to make the aqueous solution present an acidic environment to obtain an acidic solution; S2, uniformly dispersing the organosilane in the alcohol solution to obtain a mixed solution, and adding the mixed solution to a constant pressure dripping device; S3, adding the mixed solution in step S2 to the acidic solution prepared in step S1 by a constant pressure dripping device, heating after the dripping is completed, aging and alcohol removal are performed during the constant temperature process, and ultrapure aqueous solution is continuously added during the alcohol removal process to keep the quality of the solution the same as before the heating, control the pH of the solution, and obtain silica sol through a hydrolysis reaction; S4. Add ultrapure water with a resistivity of more than 18 MΩ·cm into a beaker, then add white carbon black, and stir continuously to make the white carbon black evenly dispersed in the aqueous solution to obtain a precursor silicon source seed crystal; The specific surface area of the white carbon black is 80-200 g / cm³; S5, adding the precursor silicon source seed crystal prepared in step S4 to the silica sol prepared in step S3, stirring continuously, adjusting the pH value of the solution with ammonia water, and stirring continuously for 0.5-4h by mechanical stirring; S6. Stop stirring after the gelation reaction occurs, and place at 30°C under normal pressure for 1-10 days until the gel network hardens; S7, spreading the aged gel in step S6 on a watch glass, drying it in a vacuum environment, and sieving and grading it after natural cooling; S8. Place the sample classified in step S7 in a quartz boat and calcine it at high temperature for 3-6 hours in an air atmosphere to obtain high-density quartz sand.
2. The method for preparing high-density quartz sand according to claim 1, characterized in that: In step S1, the acid solution is any one of hydrochloric acid, sulfuric acid, and nitric acid; the pH of the prepared acidic solution is 1-2; and the molar ratio of the acid solution to ultrapure water is 0.0012-0.0045:
6.
3. The method for preparing high-density quartz sand according to claim 1, characterized in that: In step S2, the organosilane is any one of tetramethoxysilane (TMOS) and tetraethoxysilane (TEOS); the alcohol solution is any one of methanol, ethanol and isopropanol; and the molar ratio of the organosilane to the alcohol solution is 1:
6.
4. The method for preparing high-density quartz sand according to claim 1, characterized in that: In step S3, the dropping speed is controlled at 0.5-8 ml / min; The constant temperature aging and alcohol removal temperature is controlled at 55°C-75°C, the time is controlled at 1-6h, and the pH is 1-2.
5. The method for preparing high-density quartz sand according to claim 1, characterized in that: In step S5, the concentration of the aqueous ammonia is 1%-27%; the speed of the mechanical stirring is 100-1600 r / min.
6. The method for preparing high-density quartz sand according to claim 1, characterized in that: In step S7, the drying temperature is 100°C-250°C; the mesh number of the sieve used for sieving and grading is 50-200.
7. The method for preparing high-density quartz sand according to claim 1, characterized in that: In step S8, the calcination temperature is 800°C-1400°C.
Citation Information
Patent Citations
High-purity quartz sand and preparation method and application thereof
CN110862091A
